Kinetics of Oxidation of myo-Inositol by Potassium Periodate in Alkaline Medium - Lakshman Kumar, Y.; Venkata Nadh, R.; Radhakrishnamurti, P.S. (Asian Journal of Chemistry, 2012)
Kinetics of oxidation of myo-inositol by potassium periodate both in alkaline and acid media were studied. The reactions were found to be first order in case of periodate in both media. In the case of base catalyzed reactions, a decrease in the rate of the reaction was observed with an increase in the concentration of substrate. An inverse fractional order with respect to substrate in alkaline shows the substrate inhibition. A positive fractional order was observed for substrate in acid catalyzed reactions. The dependence on hydrogen ions and hydroxide ions was found to be inverse fractional order. Arrhenius parameters were calculated for both the reactions conducted in acid and alkali media. Plausible mechanism is postulated based on experimental results.